Mathematical modeling of microwave drying of crashed cotton stalks for man-made composite material - Hongti, Wang; Peng, Li; Kangquan, Guo (International Journal of Agricultural and Biological Engineering, 2016)
Drying characteristics, energy consumption and drying kinetics modeling of crashed cotton stalks dried in a microwave dryer were investigated in this research. A microwave dryer with an output power of 1000 W and 2450 MHz was employed, and the effects of material load ranging from 50 g to 250 g on drying time, drying rate, drying efficiency and specific energy consumption were evaluated. The results showed that drying rate decreased with drying duration. A rising rate period was followed by a falling rate period and the overall drying process occurred in the falling rate period. Six mathematical models were used to fit the drying rates data of crashed cotton stalks, and Midilli et al. model was found the best prediction model by comparing R2, RMSE and χ2 values between experimental and predicted moisture ratios. With decrease in material load from 250 g to 50 g, effective moisture diffusivity increased from 2.8668×10-8 m2/s to 7.9817×10-8 m2/s. Results also indicated that drying efficiency and specific energy consumption significantly increased with the increase of the material load. Average drying efficiency and specific energy consumption varied in the range of 7.52%-19.78% and 12.49- 35.90 MJ/kg water, respectively. There were a lowest energy consumption of 10.99 MJ/kg water and a highest drying efficiency of 17.13% at the material load level of 250 g.Keywords: mathematical modeling, crashed cotton stalks, man-made composite material, microwave drying, kineticsDOI: 10.3965/j.ijabe.20160902.2190Citation: Wang H T, Li P, Guo K Q. Mathematical modeling of microwave drying of crashed cotton stalks for man-made composite material. Int J Agric & Biol Eng, 2016; 9(2): 171-178.